Pemanfaatan Saung sebagai Sarana Penguatan Gerakan Literasi Sekolah dalam Membangun Keterampilan Partisipasi Peserta Didik di SMK - Dani Febrianto; Cecep Darmawan; Leni Anggraeni (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
The low participation skills of students in Vocational High Schools (SMK) are a challenge in strengthening Civic Education learning. The School Literacy Movement (GLS) is seen as a strategy that not only improves reading and writing skills but also encourages active student involvement in the learning process (Ministry of Education and Culture, 2016). This study aims to describe the use of saung as a means of strengthening the School Literacy Movement in building student participation skills at SMK Texar Karawang. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation involving the principal, GLS coordinator, and students. The results show that the use of saung as a literacy space can create a more open and dialogical learning atmosphere, thus encouraging students to actively read, discuss, express opinions, and engage in literacy activities in a participatory manner. These findings indicate that saung not only functions as a physical literacy facility, but also as a social space that contributes to the development of student participation skills.